RETRACTED: Microbiome-Based Hypothesis on Ivermectin’s Mechanism in COVID-19: Ivermectin Feeds Bifidobacteria to Boost Immunity - Hazan, Sabine (Frontiers in Microbiology, 2022)
Ivermectin is an anti-parasitic agent that has gained attention as a potential COVID-19 therapeutic. It is a compound of the type Avermectin, which are fermented by-products of Streptomyces avermitilis. Bifidobacterium is a member of the same phylum as Streptomyces spp., suggesting it may have a symbiotic relation with Streptomyces. Decreased Bifidobacterium levels are observed in COVID-19 susceptibility states, including old age, autoimmune disorder, and obesity. We hypothesize that Ivermectin, as a by-product of Streptomyces fermentation, is capable of feeding Bifidobacterium, thereby possibly preventing against COVID-19 susceptibilities. Moreover, Bifidobacterium may be capable of boosting natural immunity, offering more direct COVID-19 protection. This data concords with our study, as well as others, that show Ivermectin protects against COVID-19.